Technical report: a study of heat distribution for optimal design shape of brownie's pan / Nor Shamsiah Hassan Bakri, Puteri Intan Asyura Zulkifly and Nur Ain Amirah Azman - Hassan Bakri, Nor Shamsiah; Zulkifly, Puteri Intan Asyura; Azman, Nur Ain Amirah (2017)
In this research, the heat distribution on optimal pan at the outer edges are examined. The model of heat distribution is derived from heat flux equation and energy flow balance equation by using Fourier's Law. Laplace Transform method is used to develop the model. The mathematical model of heat distribution for the optimal shape is solved in two-dimension and computerized by using MATLAB. Gauss-Seidel Iteration method is applied to approximate the temperature distribution of each nodes on the pan. It's shown from the graph and the calculation that the boundary temperature for the optimal shape is distributed evenly. Thus, the brownie does not overcooked at four comers.